PENGARUH JAMUR PHYTOPHTHORA COLOCASIAE TERHADAP PENYEBARAN VARIETAS-VARIETAS COLOCASIA ESCULENTA DI P. JAWA - YUSUF, RAZALI (BERITA BIOLOGI, 1987)
RAZALI YUSUF.1987.The influence of Phytophthora colocasiae on distribution of Colocasia esculenta varieties in Jawa island. Suppl.Berita Biologi 3 : 17 - 19.Field observation on varieties of Colocasia esculenta var.esculenta and C.esculenta var.antiquorum showed that the distribution of these two botanical varieties has distinct pattern. The population of C.esculenta var.esculenta are more prevalent in the lowland, whereas the population of C.esculenta var.antiquorum are confined to higher elevations.Differences in their succeptibility to the attack of the fungus Phytophthora colocasiae'it one important factor which determines the natural distribution of these two botanical varieties.